Space-time analysis of urban green areas in the Monterrey Metropolitan Zone, Mexico - Manzanilla-Quiñones, Ulises; Manzanilla-Quijada, Gyorgy Eduardo; Delgado-Valerio, Patricia (Ecosistemas y Recursos Agropecuarios, 2021)
Urban green areas (UGA) provide relevant ecosystem servicesto cities, unfortunately, they are vulnerable to urbanization processes. Theobjective of this study was to analyze under a spatio-temporal approachthe UGA of the Metropolitan Zone of Monterrey (MZM). Landsat and GlobalForest Change satellite images were used to estimate the UGA and environmentalquality of the MZM for the period 2000-2019. A trend (p < 0.01) ofUGA reduction was found from 2001 to 2019. The estimated environmentalquality decreased from 13.21 (2000) to 7.75 m2 (2019). The UGA area waslost at a rate of 0.29 m2 per inhabitant per year. The municipalities of Juarez,Monterrey, Apodaca and Guadalupe were the ones that lost UGA. Theconservation and protection of UGA should be priority activities for the civilauthorities of the municipalities of the MZM, specifically, in the municipality ofJuarez.